2015
DOI: 10.1007/s11192-015-1669-4
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of research progress in membrane water treatment technology from 1985 to 2013

Abstract: Research progress in membrane water treatment technology during 1985-2013 was analyzed based on the bibliometric analysis of published papers in ISI Web of Science Core Collection (Science Citation Index-Expanded, SCI-E) database, and patents in Derwent Innovation Index database. The searched data (18,075 SCI papers and 19,182 patents) were statistically analyzed from different time, countries, research institutions, mainstream technologies and application industries. The results indicated that, the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…One major aim of this study is to investigate the scientific and technological layers within the genome editing ecosystem framework so as to entangle the technologies developing clusters and growth pathways toward its market commercialization. Therefore, we analyze the publication, patent, and company database landscapes, which is one widely used approach in scientific publications to investigate and understand the emerging technologies and products ( Dai et al, 2015 ; Goeldner et al, 2015 ) and, in particular, novel technologies in the context of bio-economy ( Milanez et al, 2014 ; Berg et al, 2018 ). Real market applications of scientific knowledge and intellectual property are beneficial in terms of revenue generation, general business development, and novel goods and service market extension ( Siegel et al, 2007 ).…”
Section: Technological Innovations Are Embedded In the Context Of The...mentioning
confidence: 99%
“…One major aim of this study is to investigate the scientific and technological layers within the genome editing ecosystem framework so as to entangle the technologies developing clusters and growth pathways toward its market commercialization. Therefore, we analyze the publication, patent, and company database landscapes, which is one widely used approach in scientific publications to investigate and understand the emerging technologies and products ( Dai et al, 2015 ; Goeldner et al, 2015 ) and, in particular, novel technologies in the context of bio-economy ( Milanez et al, 2014 ; Berg et al, 2018 ). Real market applications of scientific knowledge and intellectual property are beneficial in terms of revenue generation, general business development, and novel goods and service market extension ( Siegel et al, 2007 ).…”
Section: Technological Innovations Are Embedded In the Context Of The...mentioning
confidence: 99%
“…If we go for HFM modification, then it can be found that terms such as "surface modification", "PES", "hydrophilicity" and "pore size distribution" appear most frequently and are closely related to HFM, which is also reported in the literature for the better performance of HFM with respect to biofouling. Keyword "HFM" shows a maximum link strength of 53 with keywords "PVDF" and "gas separation", followed by "ultrafiltration" (50), "PES" (39), "membrane contactor" (35), "PS" (34), "MBR" (30), "pervaporation" (27), "nanofiltration" (26), "thermally induced phase separation" (25), "water treatment" (17), "wastewater" (14) and "CO 2 separation" (13). The progressive decrease in link strength of HFM with the keywords mentioned above indicates the decreasing order of research interest of HFM in those topics.…”
Section: Clusters Analysis and Topics Of Interestmentioning
confidence: 99%
“…Miranda et al [ 24 ] presented an extensive bibliometric survey regarding the use of membranes for gas separations in petrochemical processes from 1960 to 2019 using electronic search tools, such as Google Scholar, Google Patents, USPTO and EspaceNet. Dai et al [ 25 ] also performed a bibliometric study on research progress in the area of membranes for water treatment from 1985 to 2013 using the online ISI Web of Science Core Collection database. Other than membranes, a lot of topics have been analyzed through bibliometric analysis, which shows its importance from the future prospective [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The author's keywords are an overview of the theme of an article that specifies a detailed information [12]. As the author's keyword analysis provides researchers with sufficient information on research patterns, it has proved extremely valuable in tracking the growth of research topics [13].…”
Section: Author Keywordmentioning
confidence: 99%